The vision system of the ACROBOTER project - Kouskouridas, Rigas; Kyriakoulis, Nikolaos; Chrysostomou, Dimitrios; Belagiannis, Vasileios; Mouroutsos, Spyridon G.; Gasteratos, Antonios (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2009)
The ACROBOTER project aims to develop a radically new locomotion technology that can effectively be used in a home and/or in a workplace environment for manipulating small objects autonomously. It extends the workspace of existing indoor service robots in the vertical direction, whilst its novel structure allows covering the whole volume of a room. For the adequate accomplishment of demanding manipulating tasks, its vision system must provide vital visual information concerning the position of the robot in the 3D working space and the topology of possible objects/obstacles in robot's trajectory. Thus, the proposed system is capable of: estimating robot's pose in the room; reconstruct the 3D working space and; recognize objects with remarkable efficiency. In this work, initially, we present the basic structure of ACROBOTER and its vision system and, we also evaluate the aforementioned functions. © 2009 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-07-19
Keywords: 3D Reconstruction; Object Recognition; Pose Estimation; Vision Systems